Comparative study of sinus earthquake forces and ground motion on structure behavioral response using linear time history analysis method - Suryatama Ageng Pamuji; Slamet Widodo; Maris Setyo Nugroho; Faqih Ma`arif; Ahmed Wasiu Akande (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
This study aimed to calculate the design earthquake with a harmonic sine wave approach at a frequency of 1.5 Hz; 2.5 Hz; 3.5 Hz; 4;5 Hz, as well as Loma Prieta, Northridge, and Kobe ground motion. In addition, a structural response review was also carried out based on a comparison of the effects of the ground motion and sine wave earthquake forces. This study used an experimental method of modelling an apartment building with a scale of 1: 50. The case study was located in Mantrijeron, Yogyakarta, which has a seismic category in the medium-size class. The analysis phase began with material definition, element dimension estimation, modelling by analysis software, loading estimation, structural analysis, and comparison of structural responses based on the deviation. The results indicate that the building model could withstand dynamic loads from harmonic waves up to a frequency of 5.5 Hz for one minute of vibration. The most significant deviation is shown at a frequency of 4.5 Hz with an x-axis direction of 0.110 and a y-direction of 0.160. The structural response resulting from ground motion loading shows that the highest deviation occurred due to the influence of the Kobe earthquake, with a deviation of 0.063 in the x-axis direction and 0.054 in the y-axis direction. Based on these results, the effect of harmonic sine waves is greater than the ground motion loading on the response of the building structure, so it is used as an experimental loading through a vibrating table with the actual residual deviation results showing a value of 0.9 mm in the y-axis direction. The difference in structural response results could be caused by the supports and connections modelling in planning through analysis software which could not precisely represent the actual implementation of the building model.